Development of a Method for Measuring Quasi-static Stiffness of Snowboard Wrist Protectors. (2016) - Adams, Caroline; James, David; Senior, Terry; Allen, Tom; Hamilton, Nick
Abstract: In snowboarding, the wrist is the most common injury site, as snowboarders often put their arms out to cushion a fall. This can result in a compressive load through the carpals coupled with wrist hyperextension, leading to sprains or fractures. Wrist protectors are worn by snowboarders in an effort to reduce injury risk, by decreasing impact forces and limiting wrist hyperextension during falls. However, there is no international standard or universally-accepted performance specification that these products should conform to, resulting in an inability to judge which design elements offer the most protection. EN 14120:2003 prescribes requirements that roller sports wrist protectors should meet, and has been identified as a starting point for developing a snowboarding-specific standard. This paper critiques the EN 14120:2003 test protocol and goes on to present a mechanical test for assessing the ability of snowboard wrist protectors to resist extension of the hand under an applied load. A bespoke rig incorporating the hand/arm surrogate from EN 14120:2003 was mounted to a uniaxial test machine, and wrist protectors were strapped to the surrogate at a set tightness (tight, moderate, loose). Linear displacement of the uniaxial test machine was transferred to angular displacement of the hand via a galvanised steel cable passing through a low friction pulley. Linear displacement was set to 200 mm/min and force was measured at the load cell until 80 N was reached. The test, presented here, found that the ability of the protectors to limit hand extension was dependent on how tightly they were fitted to the surrogate; therefore, strap tightness must be accounted for during further wrist protector safety assessments. This test provides a repeatable way to characterise the ability of snowboarding wrist protectors to limit wrist extension.